2009
DOI: 10.2113/jeeg14.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Investigation and Vertical Resolution of Surface Geoelectric Arrays

Abstract: Depth of investigation and vertical resolution values are determined and tabulated for 30 surface geoelectric arrays that have non-zero response, i.e., a depth of investigation characteristic (DIC) function due to a buried thin horizontal sheet. In accord with experience, results show a general reciprocal relationship between depth of investigation and vertical resolution. The most frequently used arrays in multi-electrode studies (i.e., Wenner-[Formula: see text], Wenner-[Formula: see text], Schlumberger, dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 17 publications
0
40
0
1
Order By: Relevance
“…they are not independent and are usually excluded from the data, CARPENTER and HABBERJAM, 1956). The data is collected within the same borehole (inhole) and between the two boreholes (crosshole) in vertical (v), horizontal (h) and circulating (c) modes (SZALAI et al, 2009;. HAGREY (2011) introduced two non-standard complex datasets of bhtp (sum of bh and tp-p or tripole-pole of GOES and MEEKES, 2004) and abvcs (sum of avcs and bvcs, s = symmetrical around the midpoint).…”
Section: Introductionmentioning
confidence: 99%
“…they are not independent and are usually excluded from the data, CARPENTER and HABBERJAM, 1956). The data is collected within the same borehole (inhole) and between the two boreholes (crosshole) in vertical (v), horizontal (h) and circulating (c) modes (SZALAI et al, 2009;. HAGREY (2011) introduced two non-standard complex datasets of bhtp (sum of bh and tp-p or tripole-pole of GOES and MEEKES, 2004) and abvcs (sum of avcs and bvcs, s = symmetrical around the midpoint).…”
Section: Introductionmentioning
confidence: 99%
“…Edwards (1977) found that this was in better agreement with his field experience. Szalai et al, (2009) have computed the parameter by means of both the Roy and Apparao (1971) and the Edwards' (1977) approach for all 30 arrays it was reliable. As they have found that the median depth can be determined from the Roy-Apparao depth values by a multiplication with 1.59 ± 0.31.…”
mentioning
confidence: 88%
“…Some suggest the depth of penetration of < 30% of the array length (Roy and Apparao 1971;Szalai et al 2009). Edwards (1977) suggests that the effective median depth of investigation of a dipole-dipole array is between 14 and 22% of total line length.…”
Section: Background: Electrical Resistivity Imagingmentioning
confidence: 99%